2008
DOI: 10.1254/jphs.fp0071816
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effect of Theophylline in Rats and Its Involvement of the Glucocorticoid–Glucocorticoid Receptor System

Abstract: Abstract. Although theophylline has been suggested to have an anti-inflammatory effect, there have been few reports to show the in vivo effect and the mechanism of anti-inflammatory activity of theophylline experimentally. To reveal the anti-inflammatory activity of theophylline, we studied the effect of theophylline and its metabolites on carrageenan-induced edema in rat foot pad. Subcutaneous injection of theophylline (5 -100 mg / kg) inhibited carrageenan-induced edema dose-dependently. Theophylline metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 9 publications
0
21
0
1
Order By: Relevance
“…was co-administrated with maprotiline. The doses were chosen on the basis of previous studies [4,26,27].…”
Section: Experimental Designmentioning
confidence: 99%
“…was co-administrated with maprotiline. The doses were chosen on the basis of previous studies [4,26,27].…”
Section: Experimental Designmentioning
confidence: 99%
“…Indeed, linagliptin exhibited stronger inhibitory activity and selectivity for DPP-4 compared to other inhibitors tested. Furthermore, among the nine types of DPP-4 inhibitors, linagliptin is the only one with a xanthine-based skeletal structure, and the pharmacological mechanisms underlying the anti-oxidant and anti-in ammatory activities associated with such a molecular structure remain unclear 16 . Thus, it is possible that this structural nature of linagliptin suppresses the degradation of cyclic adenosine monophosphate cAMP via phosphodiesterase inhibition thereby increasing intracellular cAMP concentration .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that an antiinfl ammatory activity of theophylline could be involved in the GC-GC receptor system. 10 In the present study, we investigated whether the GC-GC receptor system was involved in the inhibitory activity of FQs on carrageenaninduced edema, using CPFX, which has both cyclopropyl and piperazinyl groups; SPFX, which has a cyclopropyl group; and ENX, which has a piperazinyl group (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that theophylline, a well-known bronchodilator, has antiinfl ammatory activity in vivo. 10 Although roxithromycin, a 14-membered macrolide, was reported to inhibit carrageenan-induced edema in vivo, 11 very few reports have revealed the BRM activity of FQs in vivo, especially in experimental infl ammation models in experimental animals. Here, we report our study of the effect of FQs on carrageenan-induced edema in the rat footpad to reveal in vivo BRM activity and the structure-activity relationship of FQs.…”
Section: Hiromi Ogino · Kaori Yamada · Mizuki Yuhara Saori Tsuchida ·mentioning
confidence: 99%